Gin Lane - William Hogarth (Wikimedia Commons, 1806)
Notice iconographique issue de Wikimedia Commons. Titre: Gin Lane. Gin Lane, from Beer Street and Gin Lane The accompanying poem, not printed in this reissue, reads: Gin, cursed Fiend, with Fury fraught, Makes human Race a Prey. It enters by a deadly Draught And steals our Life away. Virtue and Truth, driv'n to Despair Its Rage compells to fly, But cherishes with hellish Care Theft, Murder, Perjury. Damned Cup! that on the Vitals preys That liquid Fire contains, Which Madness to the heart conveys, And rolls it thro' the Veins.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie